PENGARUH PENDIDIKAN KESEHATAN TENTANG MENSTRUASI TERHADAP KESIAPAN PSIKOLOGIS SISWI KELAS 5 DAN 6 SD DALAM MENGHADAPI MENARCHE DI MI AL ISLAM BANJAREJO MADIUN TAHUN 2016 - Ayu Purnamasari, Ika (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2017)
ABSTRACT Health education is an effort to give explanation to individual, groups or communities to foster understanding and awareness regarding healthy behaviour or a healthy life. During this period the growth and development happen quickly. On woman, puberty is marked with first menstruation (menarche), so that nowadays the information is needed through health education about menstruation in order to overcome the psychological unreadiness on the changes occun. This research aims to know the influence of health education about menstruation toward psychological readinessfifth and sixth grade students in facing menarche atMI AL Islam Banjarejo, Madiun, East Java. This research was pre experimental designs by using one group pretest posttest research designs. The population consists of a studentsof fifth and sixth grade which have not experience menstruation as many as 53 studentsatMI AL Islam Banjarejo. Sampling technique used simple random sampling on 20 respondents. The device was in the form of a questionnaire about psychological readiness of menarche with 19 questions. The statistical analysis tests used in this study was dependent t-test 2 tail. Test results of the t-tes 2 sample dependent result t count (-13262), p= 0,000 < α(0,05) so Ho is rejected and Ha is accepred. It means there is influence of health education about menstruation against psychological readines on the studentsof fifth and sixth grade in facing menarche atMI AL Islam Banjarejo, MadiunEast Javais shown by the differences of psychological readiness before (5%) and after (90%) given health education. It is expected that health education to female adolescents is given asearly as possible to overcome psychological unreadiness to face the menarche. Keywords : Health Education, Psychological readiness, Menarche